A new genus of Omaliini from China (Coleoptera: Staphylinidae: Omaliinae) - Shavrin, Alexey V. (Zootaxa, 2023)
A new omaliine genus from China is described and illustrated: Sinacrulia gen. n. The description of the genus is based on the study of two species from Yunnan, one of which was described and illustrated: S. fortiterpunctata sp. n. (Diancang Shan). The other species from Gaoligong Shan is unnamed due the absence of the male. The main morphological features of the new genus and its taxonomic relations with other genera of the tribe Omaliini MacLeay, 1825 are briefly discussed.